PENGARUH KUALITAS AKRUAL, LEVERAGE, UKURAN PERUSAHAAN DAN ARUS KAS TERHADAP CASH HOLDING PERUSAHAAN - Anjelina, Ragilia; Suhendra, Chairul; Rianindita, Nansi (Yayasan Nuraini Ibrahim Mandiri, 2023)
The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021, totaling 72 companies. The sample used in this study amounted to 19 companies using a purposive sampling technique. The data analysis technique used is the Classical Assumption Test and Partial Hypothesis Test (T Test) and Simultaneous (F Test) with the help of the SPSS 22 Program. The results of this study show partially Accrual quality (X1) has no effect on the company's cash holding with a significant value of 0.248> 0.05 (5%), Leverage (X2) has an effect on the company's cash holding with a significant value of 0.034 <0.05, Firm size (X3) has an effect on the company's cash holding with a significant value of significant 0.000 <0.05, Cash Flow (X4) has no effect on the company's cash holding with a significant value of 0.654> 0.05 (5%). While simultaneously Accrual Quality, Leverage, Company Size, and Cash Flow have a joint effect on the company's cash holding with a significant value of 0.000 <0.05 (5%).